A novel porous nanocomposite of aminated silica MCM‐41 and nylon‐6: Isotherm, kinetic, and thermodynamic studies on adsorption of Cu(II) and Cd(II). Issue 40 (23rd June 2017) - Mohammadnezhad, Gholamhossein; Soltani, Roozbeh; Abad, Saeed; Dinari, Mohammad
ABSTRACT: Porous amine‐modified MCM‐41/Nylon‐6 nanocomposite (NH2 ‐MCM‐41/NY6 NC) was synthesized by a facile solution casting protocol, which was used as an effective adsorbent for the removal of Cu(II) and Cd(II) from aqueous media. The physicochemical properties of NH2 ‐MCM‐41/NY6 NC were studied by scanning and transmission electron microscopies, thermogravimetric analysis, etc. The influence of pH, adsorbent dose, contact time and initial concentration on adsorption performance were investigated in detail. Kinetic and isotherm parameters were evaluated and the data fitted well to the pseudo‐second order and Freundlich isotherm model, respectively. The maximum adsorption capacities of Cu(II) and Cd(II) were about 35.84 and 27.5 mg·g −1, respectively. The Kd of NH2 ‐MCM‐41/NY6 NC for Cu(II) (> 10 5 m L g − 1 ) and Cd(II) (> 10 3 m L g − 1 ) ions uptake in aqueous solution, showed very good values. Thermodynamic parameters suggest that the adsorption is a spontaneous process with an endothermic nature. According to the results obtained, we conclude that this novel porous NH2 ‐MCM‐41/NY6 NC could be used for the removal of heavy metal ions from an aqueous solution. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45383. Abstract :